Micronutrient Status of Young Adolescents in Rural Bangladesh: The JiVitA-1 Birth Cohort (FS01-04-19). (13th June 2019) - Baker, Sarah; Schulze, Kerry; Wu, Lee; Shaikh, Saijuddin; Ali, Hasmot; Alland, Kelsey; Thorne-Lyman, Andrew; Mehra, Sucheta; Mitra, Maithilee; Khan, Afreen; Christian, Parul; Shaheen, Nazma; et al.
Abstract: Objectives: We assessed micronutrient status in young rural Bangladeshi adolescents to determine prevalence of deficiency by sex, age, season and dietary pattern. Methods: In a birth cohort of >30, 000 youth in whom data on health, development, and nutritional status was collected in 2015–2017, venous blood was drawn from a ∼3% subsample ( n  = 991, 9–13 years old). Participants' mothers had been in a cluster-randomized, placebo-controlled trial of daily antenatal beta-carotene or vitamin A supplementation in 2001–2007. Hemoglobin (Hb) was obtained at blood draw; plasma ferritin, folate, cobalamin (B12), homocysteine (Hcy), thyroglobulin (Tg), and C-reactive protein (CRP) were measured by chemiluminescent immunoassay, 25-hydroxyvitamin D [25(OH)D] by commercial immunoassay, and zinc by atomic absorption spectrometry. Results: Participants were short (height-for-age Z-score −1.59 ± 0.93 in boys, −1.65 ± 0.98 in girls) and thin (BMI-for-age Z-score −1.49 ± 1.06 in boys, −1.28 ± 1.08 in girls). Anemia (Hb <120 g/L, 11.4%) was common but iron deficiency (ferritin <15 μg/L, 0.5%) was not. Folate (<6.8 nmol/L, 3.3%) and vitamin B12 (<150 pmol/L, 5.2%) deficiencies, elevated Hcy (>18 μmol/L, 0.8%) and inflammation (CRP >5 mg/L, 3.3%) were uncommon. However, deficiencies of vitamin D (25(OH)D < 50 nmol/L, 43.0%), iodine (Tg > 40 µg/L, 21.9%), and zinc (<8.6 µmol/L, 18.8%) were prevalent. Only vitamin D deficiency was more prevalent in girls than boys (54.0% versus 31.4%, P  < 0.0001), doubling in girls from 32.5% at 10 to 69.7% at 13 years of age. Vitamin D deficiency was highest in winter and zinc deficiency highest during the monsoon. In preliminary analyses, micronutrient deficiencies were not significantly associated with dietary intake patterns derived from three 7-day food frequencies collected over ∼1 year. Conclusions: Young adolescents in rural northern Bangladesh experienced anemia and vitamin D, iodine and zinc deficiencies; however, iron, folate, and B12 deficiencies, hyperhomocysteinemia, and inflammation were uncommon. Further resolution of dietary data and exploration of other contextual features may reveal specific risk factors for micronutrient deficiencies, informing our understanding of adolescent nutritional status in this setting. Funding Sources: The Bill and Melinda Gates Foundation, Sight and Life.